Preparation and characterization of semi-rened carrageenan reinforced with cellulose nanofiber incorporated with a-tocopherol as an active food packaging - Wan Amnin, Wan Yahaya; Raja Nurliyana, Raja Ahmad; Nurul Aini, Mohd Azman; Ahmad Salihin, Samsudin; Wan Faizal, Wan Ishak (Universiti Malaysia Pahang, 2019)
Recent alternative in the development of bioactive packaging films which contribute both to reduce waste disposal problems and prolong shelf life of food have received attention among consumers. Semi-refined carrageenan (SRC) based film plasticized with glycerol (G) reinforced with different concentration cellulose nanofibre (CNF) (2%, 5%, 7%, and 10% [w/w]) incorporated with 0.4% (w/w) α-tocopherol were prepared for food packaging application. Functional mechanical and physical properties of SRC-based films were characterized. The release of antioxidant α-tocopherol from SRC-based film were studied based on total phenolic content (TPC) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) throughout 31 day storages. FTIR spectra analysis provided some insight interaction between SRC, glycerol, CNF and antioxidant α-tocopherol. The result shows incorporation of CNF increased the mechanical properties of SRC-based film when compared to the control film. The filling effect of CNF caused an increase in elongation and tensile strength. When a high content of CNF (10%) was incorporated in the films, the water solubility was decreased due to the reduction of hydrophilic domains in the film matrix. Moreover, addition of α-tocopherol into films contained phenolic compounds displayed strong antioxidant activities. These results demonstrate that CNF and α-tocopherol can significantly enhance the mechanical properties, antioxidant ability, and reduce the water solubility of SRC-based films that can be used as an active food packaging material. Hence, the incorporation of CNF into SRC-based film could be an alternative way to replace non-biodegradable plastic whilst reduce the use of synthetic antioxidant directly into food product.